1988
DOI: 10.1111/j.1699-0463.1988.tb00987.x
|View full text |Cite
|
Sign up to set email alerts
|

A streptococcal plasminogen activator in the focus of infection and in the kidneys during the initial phase of experimental streptococcal glomerulonephritis

Abstract: streptococcal plasminogen activator in the focus of infection and in the kidneys during the initial phase of experimental streptococcal glomerulonephritis.Strains of group A streptococci known to secrete the nephritis strain-associated protein (NSAP), a plasminogen activator, were studied for their ability to produce APSGN in rabbits. A tissue cage model was used to monitor the secretion of NSAP at the focus of infection and histopathological examination of kidney tissue was used to determine glomerular pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The acquisition of this activity may have pleiotrophic effects on the pathogenesis of infection, any or all of which may be relevant to infection and induction of mastitis in the ruminant mammary gland. Activation of plasminogen may facilitate bacterial invasion due to hydrolysis of extracellular matrix proteins [14], reduce immunity due to the hydrolysis of immunoglobulin [15] and/or induce inflammation due to the activation of the complement cascade [16].…”
Section: Resultsmentioning
confidence: 99%
“…The acquisition of this activity may have pleiotrophic effects on the pathogenesis of infection, any or all of which may be relevant to infection and induction of mastitis in the ruminant mammary gland. Activation of plasminogen may facilitate bacterial invasion due to hydrolysis of extracellular matrix proteins [14], reduce immunity due to the hydrolysis of immunoglobulin [15] and/or induce inflammation due to the activation of the complement cascade [16].…”
Section: Resultsmentioning
confidence: 99%
“…Holm et al [97][98][99] suggested that NSAP contributed to the pathogenesis of PSAGN via its ability to convert plasminogen to plasmin, which cleaves C3, thus activating the alternative complement pathway and contributing to glomerular inflammation. Others suggested that active plasmin could induce PSAGN via degradation of extracellular matrix proteins and activation of matrix metalloproteinases [52,100].…”
Section: Pathogenesismentioning
confidence: 98%
“…Strains which did not contain the nephritis-associated protein did not cause glomerulonephritis or glomerular deposits. Further studies by Holm and colleagues investigated the osmotic pump model, in which small amounts of the nephritis strain-associated protein were released slowly into the animal, with development of acute glomerulonephritis (243). A most recent report describes deposition of streptokinase and the C3 component of complement in the glomeruli of BALB/c mice implanted with tissue cages infected with the nephritogenic NZ131 and EF514 strains (387).…”
Section: Nonsuppurative Sequelae Acute Poststreptococcal Glomerulonepmentioning
confidence: 99%